STUDI LITERATUR: MENINGKATKAN KETERAMPILAN SOSIAL MELALUI MODEL PEMBELAJARAN KOOPERATIF TEAMS GAMES TOURNAMENT (TGT) PADA PEMBELAJARAN IPS DI SEKOLAH DASAR - Siska Dwi Maryani; Selly Alvira, Yolanissa; Juhana Sakmal; Engga Dallion (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to find out how to improve social skills through the Teams Games Tournament (TGT) cooperative learning model in social studies learning in elementary school. This research uses the literature study method by searching for sources such as scientific articles, journals or documents related to research problems. Based on the data of 10 journal articles analyzed, it can be concluded that the Teams Games Tournament (TGT) Cooperative Learning Model can improve social studies social skills in elementary schools in Indonesia. In its implementation, the TGT model with its advantages makes students get a better influence to improve their social skills so that students become more skilled in socializing including the ability to socialize, collaborate, cooperate, communicate, and interpersonal intelligence.